Tinjauan Yuridis Mengenai Hak-Hak Khusus Pekerja Perempuan Berdasarkan Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan - Sonhaji Sonhaji (Administrative Law and Governance Journal, 2019)
Abstract Women are naturally different from the men so that women have special rights granted while men are not given. Female workers/laborers likewise have special rights such as the right to leave miscarriage, the right to maternity leave, menstrual leave, the right to a shuttle if employed at night, and so forth. The special rights of female workers/laborers like these should be considered either by the company or by the workers/laborers women themselves. PT. Dian Andilta Utama is not yet fully apply the special rights of female workers/laborers, obstacles in implementing the special rights of female workers/laborers are in the application of the provision of menstrual leave and leave miscarriage, efforts to overcome obstacles in the implementation of the exclusive rights of female workers/laborers are female workers/laborers should correctly understand the content of the employment agreement is given at the beginning will sign a cooperation agreement. Keywords: Special Rights Of Women Workers, Act No. 13 of 2003 Abstrak Perempuan secara kodrati berbeda dengan laki-laki sehingga perempuan memiliki hak-hak khusus yang diberikan sedangkan laki-laki tidak diberikan.Pekerja/ buruh perempuan demikian pula memiliki hak-hak khusus seperti hak cuti keguguran kandungan, hak cuti melahirkan, hak cuti haid, hak mendapatkan antar jemput jika dipekerjakan pada malam hari, dan sebagainya.Hak-hak khusus pekerja/ buruh perempuan seperti ini sudah seharusnya diperhatikan baik oleh pihak perusahaan maupun oleh para pekerja/ buruh perempuan itu sendiri. PT. Dian Andilta Utama belum sepenuhnya menerapkan hak-hak khusus pekerja/ buruh perempuan, hambatan dalam menerapkan hak-hak khusus pekerja/ buruh perempuan adalah dalam penerapan pemberian cuti haid dan cuti keguguran, upaya mengatasi hambatan dalam penerapan hak-hak khusus pekerja/ buruh perempuan adalah pekerja/ buruh perempuan harus memahami secara benar isi dari perjanjian kerja yang diberikan pada saat awal akan menandatangani perjanjian kerja. Kata kunci: Hak-Hak Khusus Pekerja Perempuan, Undang-Undang Nomor 13 Tahun 2003